Media Use During COVID-19: An Investigation of Negative Effects on the Mental Health of Asian Versus White Americans - Quintero Johnson, Jessie M.; Saleem, Muniba; Tang, Lu; Ramasubramanian, Srividya; Riewestahl, Emily (Frontiers in Communication, 2021)
The role of media use on mental health distress is particularly concerning during the COVID-19 global pandemic. The vulnerabilities to and experiences of the COVID-19 pandemic in the United States are greatly influenced by racial/ethnic inequalities. The COVID-19 pandemic may present unique mental health challenges for Asian Americans because of racial targeting and limited access to and engagement with mental health care. This present investigation examines whether the association between media use and mental health distress is more pronounced for Asian Americans for whom media messages that document and promote anti-Asian racism are likely to be especially salient and influential. Using a national survey of Asian (N = 524) and White (N = 527) American participants, our findings reveal that racial/ethnic identity interacted with the negative effect of media use on mental health for Asian Americans, but not for White Americans. We also explored whether the effect of media use on mental health was mediated by social and health risk perceptions. Results revealed that even though imagined stigma was associated with mental health distress, it did not mediate the effect of media use on mental health. Health risk perceptions mediated the negative effect of media use on both psychosocial distress and loneliness. Implications for health communication, media studies, and anti-Asian racism are discussed, especially in the context of health crises.